Ftir and Raman Characterization of tio2 Nanoparticles Coated with Polyethylene Glycol as Carrier for 2-Methoxyestradiol - Orihuela-Diaz, P; Reuquen-Lopez, P; Zapata-Ramirez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
The aim of this study was to prepare a novel targeting drug delivery system for 2-Methoxyestradiol (2ME) in order to improve the clinical application of this antitumor drug. It is based in nanoparticles (NPs) of titanium dioxide (TiO2) coated with polyethylene glycol (PEG) and loaded with 2ME. A complete IR and Raman characterization have been made to confirm the formation of TiO2-PEG-2ME composite. Vibrational modes have been assigned for TiO2, PEG, and 2ME and functionalized TiO2-PEG and TiO2-PEG-2ME. The observed variation in peak position of FTIR and Raman of each for these composites has been elucidated in terms of intermolecular interactions between PEG-2ME and TiO2, obtaining step-by-step the modification processes that were attributed to the conjugation of PEG and 2ME to TiO2 NPs. Modifying TiO2 NPs with PEG loaded with the 2ME drug revealed that the titanium dioxide nanocarrier possesses an effective adsorption capability, and we discuss their potential application as a system of drug delivery. © 2016 by the authors.